KEANEKARAGAMAN JENIS DAN INTENSITAS SERANGAN RAYAP TANAH DI TIGA TIPE TANAH DI AREAL BEKAS KEBUN KARET - Ginuk Sumami; Agus Ismanto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
This paper deals with a study on the infestation intensity of subterranean termites on three soil types in clear felled rubber plantation areas in West Java. The soil types predominating the areas are Red Podzolic, Brown Latosol and Dark Grey Grumusol. The results reveal that four species of termite Microtermes insperatus Kemner, M. incertoides Holmgren, Macrotennes gilvus (Hagen) and Capritermes buitenzorgi Holmgren are found in these areas pie termites were mostly found on the Dark Grey Grumusol soil, and the least number of termite was found at the Red Podzolic soil.The results also reveal that the soil type gave significant effect to the infestation intensity of subterranean termite, but it did not give any effect to the community of the termite.